2020
DOI: 10.2147/idr.s287224
|View full text |Cite
|
Sign up to set email alerts
|

Transfusion Transmissible Infections Among Voluntary Blood Donors at Dessie Blood Bank, Northeast Ethiopia: Cross-Sectional Study

Abstract: Background The prevalence of transfusion transmitted infections (TTIs) among blood donors varies across different geographical populations. Establishing the sero-prevalence of the disease among blood donors is important to informing the direction of preventive and control strategies. Objective The aim of this study was to determine the sero-prevalence of transfusion transmitted infections among voluntarily blood donors at Dessie Blood Bank, North East Ethiopia. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
6
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 32 publications
5
6
2
Order By: Relevance
“…These developments could be due to limited exposure to sexual education, as well as exposure to drug elicitation among the younger generation (25). Similar to study in Ghana (19), but in contrast to studies in Ethiopia (12,13,22), the named infections were more prevalent among female than male donors in our study. The relatively higher rates of TTIs among female in this study could be due to the natural anatomic limitations associated with female sexual organs, which often compromise the innate defense system (26).…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…These developments could be due to limited exposure to sexual education, as well as exposure to drug elicitation among the younger generation (25). Similar to study in Ghana (19), but in contrast to studies in Ethiopia (12,13,22), the named infections were more prevalent among female than male donors in our study. The relatively higher rates of TTIs among female in this study could be due to the natural anatomic limitations associated with female sexual organs, which often compromise the innate defense system (26).…”
Section: Discussionsupporting
confidence: 88%
“…The relatively higher proportion of donors age 20-29 (56.0%) was similar to studies in Ethiopia (12,13). The reasons attributed for these development included the dependency on secondary school and college students to sustain the blood banks (8,9).…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…The present study indicated that HBV (2.95%) is the most prevalent infection among blood donors in Afghanistan. This is comparatively lower than studies from neighboring countries, India 23 (3.44%) and Pakistan 24 (3.91%), and those reported from Ethiopia 25 (4.2%). This may be attributed to the effective prevention and control mechanisms including mandatory vaccination programmes.…”
Section: Discussioncontrasting
confidence: 60%
“…The residual risk of HIV is a problem that daily threatens the safety of donation in all blood banks around the world. The transmission of transfusion-transmissible infections (TTIs) remains a real problem in transfusion settings around the world [ 1 5 ].…”
Section: Introductionmentioning
confidence: 99%